Active DNA demethylation is required for complete imprint erasure in primordial germ cells - Kawasaki, Yuki (Nature Publishing Group, 2014)
In mammalian primordial germ cells (PGCs), DNA demethylation is indispensible for parental imprint erasure, which is a reprogramming process essential for normal developmental potential. Thus, it is important to elucidate how DNA demethylation occurs in each imprinted region in PGCs and to determine which DNA demethylation pathway, passive or active, essentially contributes to the erasure of the imprint. Here, we report that active DNA demethylation via a putative Poly(ADP-ribose) polymerase (PARP) pathway is involved in H19-DMR imprint erasure in PGCs, as shown by an in vivo small molecule inhibitor assay. To the best of our knowledge, this is the first direct demonstration of a DNA replication-independent active DNA demethylation pathway in the erasure process of genomic imprinting in PGCs in vivo. The data also suggest that active DNA demethylation plays a significant role in the complete erasure of paternal imprinting in the female germ line.